Prognostic impact of donor mitochondrial genomic variants in myelodysplastic neoplasms after stem-cell transplantation - Jing Dong; Shahram Arsang-Jang; Tao Zhang; Zhongyuan Chen; Yung-Tsi Bolon; Stephen Spellman; Raul Urrutia; Paul Auer; Wael Saber (Journal of Hematology & Oncology)
Abstract Mitochondrial DNA (mtDNA) variants in patients with myelodysplastic neoplasms (MDS) are shown to be prognostic of outcomes after allogeneic hematopoietic cell transplantation (allo-HCT). However, the prognostic impact of donor mtDNA variants is unknown. Here, we performed whole-genome sequencing on 494 donors who were matched to MDS patients enrolled in the Center for International Blood and Marrow Transplant Research (CIBMTR). We evaluated the impact of donor mtDNA variants on recipients’ transplantation outcomes, including overall survival, relapse, relapse-free survival, and transplant-related mortality. The optimism-adjusted bootstrap method was employed to evaluate the prognostic performance of models that include donor mtDNA variants alone and combined with MDS- and HCT-related clinical factors. In the entire donor cohort, we identified 1,825 mtDNA variants, including 67 potential pathogenic variants. Genetic variants on MT-CYB and MT-ND5 genes were identified as independent predictors of posttransplant outcomes. Integration of donor mtDNA variants into the models based on the International Prognostic Scoring System-Revised (IPSS-R) could capture more prognostic information for MDS patients. Sensitivity analysis in 397 unrelated donors obtained similar results. More importantly, we found that incorporating donor mtDNA variants with donor age and the degree of HLA-matching could help to identify “suboptimal” younger HLA-well-matched unrelated donors and “optimal” older HLA-partially/mismatched unrelated donors. Our study shows that mtDNA variants in donors, including those from unrelated donors, hold prognostic value for MDS patients undergoing allo-HCT and augment the prognostic stratification of current scoring systems. These findings present an opportunity to refine donor selection strategies and improve posttransplant outcomes for MDS patients.